2016
DOI: 10.1007/s00216-016-9623-8
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the in vitro uptake mechanism and antioxidant levels in HaCaT cells and resultant changes to toxicity and oxidative stress of G4 and G6 poly(amidoamine) dendrimer nanoparticles

Abstract: 20The mechanism of cellular uptake by endocytosis and subsequent oxidative stress has been 21 identified as the paradigm for the toxic response of cationically surface charged nanoparticles. In 22 an attempt to circumvent the process, the effect of increased cellular membrane permeability on 23 the uptake mechanisms of poly (amidoamine) dendrimers generation 4 (G4) and 6 (G6) in vitro 24 was investigated. Immortalised, non-cancerous human keratinocyte (HaCaT) cells were treated 25 with DL-Buthionine-(S,R)-sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…the impact of membrane asymmetry, which is found in most cellular membranes, on interactions between bilayers and dendrimers. It also highlights the ability of dendrimers to translocate passively through cellular membranes, as observed by several others experimentally [14,57,85].…”
Section: Coarse-grained Simulationssupporting
confidence: 65%
See 3 more Smart Citations
“…the impact of membrane asymmetry, which is found in most cellular membranes, on interactions between bilayers and dendrimers. It also highlights the ability of dendrimers to translocate passively through cellular membranes, as observed by several others experimentally [14,57,85].…”
Section: Coarse-grained Simulationssupporting
confidence: 65%
“…The size of these dendrimer-lipid aggregates has been measured using DLS and it was found that lipid bilayers wrap around higher generation dendrimers (>G5) forming 'dendrisomes'. Using NR, dendrimers have been found to translocate through SLBs, which indicates the possibility of passive transfer through cell membranes as suggested by in vitro studies discussed in Section 3 [57]. The energetics of these interactions has been explored using DSC and Raman spectroscopy, revealing changes in the fluidity of lipid acyl chains in the presence of dendrimers dependent upon dendrimer generation and charge.…”
Section: Interactions Between Pamam Dendrimers With Supported Lipid Bmentioning
confidence: 96%
See 2 more Smart Citations
“…[16][17][18] The toxic effects of the PAMAM dendrimers on different cell lines have also been widely studied using cytotoxicity assays such as Alamar Blue (AB), MTT, Neutral Red (NR) and Clonogenic assays. [19][20][21][22][23][24] Cellular exposure to PAMAM dendrimers has been shown to result in oxidative stress, activation of inflammatory cascades. As a general mechanism, dendrimers are found to cause a generation dependent, systematic cytotoxicity, oxidative stress and genotoxicity due to the proton sponge effect in endosomes and/or lysosomes, which causes lysosomal rupture and mitochondrial accumulation, resulting in cell death.…”
Section: Introductionmentioning
confidence: 99%